The Twelve Days of Dissolution:Ibn Khaldun's Theory of State Cycles and the Swift Collapse of the Syrian Regime - Habib Badawi (CV. FOUNDAE, 2025)
This study examines the rapid collapse of the Syrian regime through the theoretical lens of Ibn Khaldun's concept of 'asabiyyah (group solidarity) and state cycles. It investigates how a seemingly stable authoritarian structure experienced sudden systemic failure within a twelve-day period. By synthesizing classical Islamic political theory with contemporary frameworks of state failure, this research provides novel insights into the mechanisms of state decay and rapid regime collapse. Through careful analysis of primary sources and theoretical frameworks from both classical Islamic and modern political theory, the study reveals that the regime's swift collapse followed patterns predicted by Ibn Khaldun's theory, particularly regarding the relationship between institutional sophistication and political vulnerability.